2015
DOI: 10.17219/acem/38143
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase GSTM 1, Null Genotype May Be Associated With Susceptibility to Age-Related Cataract

Abstract: Background. Age-related cataract (ARC) is the leading cause of visual disability and reversible blindness all over the world. The different expressions of GST isozymes among animals may explain the variations in the cataract formation caused by oxidative stress. Objectives. In this study, we evaluated the distribution of GST gene polymorphisms in ARC patients and the possible associations between the presence of ARC and GST gene polymorphisms. Material and Methods. The epidemiological data was collected by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…GST has also been described as a glaucoma associated stress marker, and increased serum GST immunoreactivity was reported in glaucoma patients. Furthermore, polymorphisms of selected GSTs such as GSTM1 and GSTT1 were shown to be associated with the onset and development of glaucoma 82 , 83 , cataract 84 , 85 , PD 86 , 87 and AD 88 .…”
Section: Discussionmentioning
confidence: 99%
“…GST has also been described as a glaucoma associated stress marker, and increased serum GST immunoreactivity was reported in glaucoma patients. Furthermore, polymorphisms of selected GSTs such as GSTM1 and GSTT1 were shown to be associated with the onset and development of glaucoma 82 , 83 , cataract 84 , 85 , PD 86 , 87 and AD 88 .…”
Section: Discussionmentioning
confidence: 99%
“…The cellular mechanisms of age-related ocular disorders, such as age-related macular degeneration (AMD) [3, 4, 14, 25], diabetic retinopathy [19, 23, 41], glaucoma [1, 9, 11], and cataracts [5, 37], are tightly associated with oxidative stress, inflammation, and the unfolded protein response (UPR), suggesting cross talk between these cellular signals. Oxidative stress has been found to play a deteriorating role in aged retinas by producing reactive oxygen species (ROS) that are known to trigger different retinopathies, causing damage to the mitochondrial DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The cDNAs encoded by GSTM1 and GSTM2 share a remarkable 99% sequence identity. The fact that GSTM1 and GSTM2 are physically linked suggests that the frequent deletion of the GSTM1 locus is caused by unequal crossing-over 15,16 . Furthermore, in HeLa cells, it has been confirmed that GSTM2 overexpression, following transient knockdown of GSTM1 and the absence of GSTM1 activity, may be compensated by the overexpression of GSTM2 17 .…”
Section: Introductionmentioning
confidence: 99%